Stratospheric temperatures during AASE - Results from STRATAN - Rood, Richard B.; Newman, Paul A.; Lait, Leslie R.; Lamich, David J.; Chan, K. Roland (1990)
Comparisons of temperatures from the research analysis STRATAN to radiosonde data, Meteorological Measurement System (MMS) data, and the National Meteorological Center (NMC) analyses are presented for the Airborne Arctic Stratospheric Expedition (AASE). The STRATAN analyses show consistent quality throughout AASE. The comparisons to MMS show that STRATAN more accurately represented low temperatures than NMC. This, coupled with forecast quality, show that STRATAN temperature fields are a valuable tool for diagnosing and forecasting polar stratospheric clouds.